Chemodivergent Dehydrative Nucleophilic Substitutions of Diarylmethanols with 1‐Phenyl‐1H‐tetrazole‐5‐thiol Catalyzed by FeCl3. Issue 8 (16th July 2020) - Oda, Ryoga; Nakata, Kenya
Abstract: Chemodivergent dehydrative nucleophilic substitutions of diarylmethanols with 1‐phenyl‐1 H ‐tetrazole‐5‐thiol were achieved using FeCl3 as a catalyst in MeNO2 by changing reaction temperature. It was found that sulfur nucleophilic attack occurred to afford kinetically controlled products that rearranged into thermodynamically controlled products. A variety of diarylmethanols could be applied to the reaction, irrespective of the substituents on the aromatic rings of the substrates. It was also revealed that the reactions of several kinds of alkyl‐ and heteroaryl‐substituted benzyl alcohols gave moderate to good product yields. The controlled experiments performed revealed that both reactions proceeded in an SN 1 fashion and heating with a Lewis acid was necessary for rearrangement. Abstract : FeCl3 ‐catalyzed chemodivergent nucleophilic substitutions of diarylmethanols with 1‐phenyl‐1 H ‐tetrazole‐5‐thiol were achieved by adjusting the reaction temperature. Kinetically controlled thiotetrazoles were produced by sulfur nucleophilic attack, whereas thermodynamically controlled thioterazoles were obtained by nitrogen nucleophilic attack.